2005
DOI: 10.1111/j.1464-410x.2005.05735.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of medical therapy on surgery for benign prostatic hyperplasia: a study comparing changes in a decade (1992–2002)

Abstract: OBJECTIVESTo compare the clinical profile (age, comorbidities, symptom severity, and incidence of acute urinary retention, AUR), the type and duration of medical treatment, and indications for surgery of patients undergoing surgery for benign prostatic hyperplasia (BPH) in 1992 and 2002 at one centre. PATIENTS AND METHODSIn this single-centre, retrospective, crosssectional observational study, the medical history of all patients who had surgery for BPH in the first semester of 1992 (85) and 2002 (70) was revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
1
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 28 publications
3
38
1
6
Order By: Relevance
“…Despite the initial recommendations by Nesbit (5), historical data has shown that the amount of resected tissue has decreased significantly over time (7,8). In the study of Borth et al (7), mean weight of tissue resected in 1988 was 16.5g and decreased to 12.5g in 1998.…”
Section: Commentsmentioning
confidence: 98%
See 1 more Smart Citation
“…Despite the initial recommendations by Nesbit (5), historical data has shown that the amount of resected tissue has decreased significantly over time (7,8). In the study of Borth et al (7), mean weight of tissue resected in 1988 was 16.5g and decreased to 12.5g in 1998.…”
Section: Commentsmentioning
confidence: 98%
“…The recommended technique of TURP consists of complete removal of all adenomatous tissue inside the surgical capsule (5). However, complication rates seem to be related to resection time and the amount of resected tissue (6), and historical data has shown that the amount of resected tissue during TURP has decreased significantly over the last 10 years (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…20 Longer medical treatment for BPH has been associated with a decreased number of patients undergoing BPH surgery resulting in increased prostate volume with potentially more patients needing open surgery. 21 The question is whether changes in laser surgery over the past 16 years have been able to sustain surgical outcome despite significant changes in the target population. Fortunately, the currently available new laser technology and equipment confer benefits to these patients and could overcome the challenge of increased prostate volume and patient comorbidities.…”
mentioning
confidence: 99%
“…However, it takes a few months before clinical improvement is apparent. [14][15][16][17][18][19][20][21][22] The value of combination therapy with 5ARIs and ablockers over monotherapy with either drug was first demonstrated in the Medical Therapy Of Prostatic Symptoms (MTOPS) study. 23 In men with BPH, combination therapy with finasteride and doxazosin was superior to each monotherapy at 4 years for treatment of LUTS and reducing risk of progression.…”
Section: Introductionmentioning
confidence: 99%